Pelatihan Kewirausahaan di Kalangan Remaja di Desa - Herman Syahruddin; Nuryamsu Nuryamsu; Djamilah Saleh; Ruslan Ahmad; Arifin Idrus; Andi Pattiware; Abd. Rajab; Firmansyah Firmansyah (Institut Nalanda, 2024)
This community service activity aims to improve the knowledge and skills of teenagers in business management. The activity was made in the form of training and mentoring which was carried out for 2 days and was carried out in the hall of the Sanrobone village office, Sanrobone district, Takalar district and was attended by 22 teenagers. This entrepreneurship training was carried out by STIEM Bongaya Makassar and the Sanrobone village government. The methods used in this service activity include the lecture method at the socialization stage on the understanding and knowledge of business management or management, the discussion method for the business management understanding stage. Based on the results of community service activities, results were obtained in the form of the need for support and space for teenagers to develop their entrepreneurial spirit. Training and mentoring to improve management skills or business management are activities that must be done to help teenagers in running their businesses. The role of campuses in helping youth entrepreneurs must be sustainable.